PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA MELALUI PENERAPAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING - Lena Rosdiana Pangaribuan (Universitas Islam Sumatera Utara, 2023)
One of the abilities that is expected to be owned by every student in every mathematical learning process is the ability to think critically. This research is experimental research that examines Contextual Teaching and Learning in an effort to improve students' mathematical critical thinking skills conducted at SMA Negeri 15 Medan with a sample of class X Science as many as two classes taken randomly. The instrument used in this study was a test of students' critical thinking skills to determine students' critical mathematical abilities. The results of the study can be concluded that the critical mathematical abilities that receive Contextual Teaching and Learning learning experience a better increase than those that receive conventional learning. Based on the results of the study it can be concluded that the application of Contextual Teaching and Learning learning is effective for improving students' mathematical critical thinking skills and students' active activities.